PENGARUH PENGGUNAAN KATA SAPAAN DI LINGKUNGAN PEKERJAAN UNIVERSITAS HARAPAN MEDAN - Handini, Frida Dian; Mauluddya, Tania (Universitas Quality, 2023)
This research was a descriptive qualitative that aimed to find out the effect of using greeting words in the work environment. The subject of this research was employees in Harapan University Medan. The object was utterances uttered by the employees in Harapan University Medan. To collect the data, the researcher did the observation and also interviewed the employees. The data was analyzed by using Interactive Mode by Miles, Huberman, and Saldana whicb consisted of some steps, they are: collecting data, condensation, presence, and draw the conclusion.